Breast effects of oral, combined 17β-estradiol, and progesterone capsules in menopausal women: a randomized controlled trial. Issue 12 (December 2020) - Liu, James H.; Black, Denise R.; Larkin, Lisa; Graham, Shelli; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: To evaluate the effect of a single-capsule, bioidentical 17β-estradiol (E2) and progesterone (P4) hormone therapy on mammograms and breasts in postmenopausal women after 1 year of use. Methods: In the 12-month, phase 3, randomized, double-blind, placebo-controlled, multicenter REPLENISH trial, postmenopausal women (40-65 y) with moderate to severe vasomotor symptoms and a uterus were randomized to four active daily dose groups of E2/P4 (TX-001HR) or a placebo group. Mammograms were performed and read locally at screening (or ⩽6 months before first dose) and at study end using BI-RADS classification. Incidence of abnormal mammograms and breast adverse events was evaluated. Results: All but 8 (0.4%) mammograms at screening were normal (BI-RADS 1 or 2). At 1 year, 39 (2.9%) of the 1, 340 study-end mammograms were abnormal (BI-RADS 3 or 4); incidence was 1.7% to3.7% with active doses and 3.1% with placebo. Breast cancer incidence was 0.36% with active doses and 0% with placebo. Breast tenderness was reported at frequencies of 2.4% to 10.8% with active doses versus 0.7% with placebo, and led to eight study discontinuations (1.6% of discontinuations in active groups). Conclusions: In this phase 3 trial of a combined E2/P4, results of secondary outcomes suggest that E2/P4 may not be associated with increased risk of abnormal mammograms versus placebo, and the incidence of breast tenderness was low relative to most of the rates reported in other studies using hormone therapy.